Integrating Evaluation Into Counselling Practice: Accountability and Evaluation Intertwined - Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2007)
Evaluation needs to be seen as an integral part of counselling—an activity that is interwoven with intervention rather than an added extra. This will require developing new ways to gather evidence attesting to client change that document the processes in which counsellors and clients engage and the outcomes associated with those processes. It will also necessitate developing an expanded, collaborative model for evaluation that involves working with stakeholders to determine what evidence will be appropriate, the evaluation methods and timelines, and ways of disseminating the evaluation results.